Simultaneous fault detection and control design for switched linear systems based on dynamic observer. (2nd December 2011) - Davoodi, M.R.; Golabi, A.; Talebi, H.A.; Momeni, H.R.
SUMMARY The problem of simultaneous fault detection and control (SFDC) for linear continuous‐time switched systems is addressed in this paper. An H ∞ formulation of the SFDC problem using dynamic observer is presented. In essence, a single unit called detector/controller depending on the system modes is designed, where the detector is a dynamic observer, and the controller is a state feedback controller based on the dynamic observer. It is shown that the dynamic observer can be used effectively to tackle the drawbacks of the existing methods of SFDC design. Extended linear matrix inequalities (LMIs) characterization is used to reduce the conservativeness by introducing additional matrix variables, so as to eliminate the coupling of Lyapunov matrices with the system matrices. Indeed, the idea presented in this paper is based on average dwell time and conservatism reduction approaches and applying the advantages of dynamic observers, which leads to some sufficient conditions for solvability of the SFDC problem in terms of LMI feasibility conditions. Simulation results illustrate the effectiveness of the proposed design methodology. Copyright © 2011 John Wiley & Sons, Ltd.